Physiotherapy in Primary Care in Brazil based on a Quality Assessment Program: cross-sectional study (Research, Society and Development, 2021)
Objectives: analyze the presence of physical therapists in the minimum Primary Health Care teams in the five regions of Brazil and to compare the presence of equipment directed to their performance. Methods: a cross-sectional study using data from Module I of the 3rd Cycle of the Quality Assessment Program in Primary Care from Primary Care Units where physical therapists worked in. The association between the presence of physiotherapist and greater equipment in the units was assessed using the Chi-Square Test. Results: In all of Brazil, 26.3% of the Units had another professional working in addition to the Primary Care Team, and among these, 24.8% was physiotherapist. It was observed that, compared to the national proportion, the Northeast Region had the highest proportion of inserted professionals (p = 0.017). An association was observed between the presence of the professional and equipment, with some specific ones more present in places with physiotherapists (p < 0.05). Conclusions: The number of physiotherapists working together with the Primary Care Teams in Brazil is low. However, their work with the population signals new professional possibilities for action.